1971
DOI: 10.1139/m71-064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiation pasteurization on Salmonella. III. Radiation lethality and the frequency of mutation to antibiotic resistance

Abstract: The radiation resistance (D, in megarads) of six strains of Salmonella irradiated at 4C in brain heart infusion suspension ranged from 0.042 for S. enteritidis to 0.084 for S. thompson. The resistance values were 0.048 for S. typhimurium, strain SR-11, 0.060 for S. typhimurium, strain RIA, and S. newport, and 0.078 for S. heidelberg. The mutation frequency to tetracycline resistance of S. typhimurium, strain SR-11, increased between 0 and 0.05 Mrad and declined thereafter with increasing radiation dose. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In other bacteria, one or more doses of radiation can cause an increase in radiation resistance (132,358,481), an increase in antibiotic resistance (498), morphological changes (173,358), biochemical changes (173), and decreased pathogenicity (180,498). Irradiated or chemically treated D. radiodurans cells usually give rise to colonies identical to those of unirradiated bacteria, although some colonies are smaller, pigmentless, and rough with irregular edges (161,434).…”
Section: Ionizing Radiation Resistance Of D Radioduransmentioning
confidence: 99%
“…In other bacteria, one or more doses of radiation can cause an increase in radiation resistance (132,358,481), an increase in antibiotic resistance (498), morphological changes (173,358), biochemical changes (173), and decreased pathogenicity (180,498). Irradiated or chemically treated D. radiodurans cells usually give rise to colonies identical to those of unirradiated bacteria, although some colonies are smaller, pigmentless, and rough with irregular edges (161,434).…”
Section: Ionizing Radiation Resistance Of D Radioduransmentioning
confidence: 99%
“…(2) Three Indian studies showed abnormal white blood cells in children and monkeys and rats fed irradiated wheat (Baskaram and Sadasivan 1975;andVijayalaxmi 1975 and. (3) Two Indian studies showed that irradiated wheat, maize, sorghum, pearl millet, potatoes, and onions produced more aflatoxins than the non-irradiated samples Tulepule 1976 and.…”
Section: Public Acceptancementioning
confidence: 99%
“…No chromosomal effects from consumption of irradiated poultry meat could be discerned. (Tracor Jitco, Inc. 1983) In the aflatoxin studies by Tulepule (1976 and the samples were heat sterilized before infection with fungi. Such a heat sterilization process, like many other food processes, destroys natural antifungal conponents in the food (Sharma et aZ1981).…”
Section: Public Acceptancementioning
confidence: 99%
See 2 more Smart Citations